FIELD STUDY OF HEAT AND DROUGHT RESISTANCE OF CHICKPEAS VARIETIES AND SAMPLES IN RAINFRIED AREAS SOUTHERN INSTITUTE OF AGRICULTURAL SCIENTIFIC RESEARCH (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
During the growth and development of cultivated plants in agriculture, an increase in soil moisture and relative air humidity can cause various diseases during the plant development stage. If the plant is exposed to heat and drought, the number of stems of the plant will decrease, the productivity will decrease and the grain quality indicator will be Therefore, one of the urgent problems of today is the creation of crop varieties resistant to biotic and abiotic factors. low. Therefore, one of the urgent problems of today is the creation of crop varieties resistant to biotic and abiotic factors.